Enhancing Creativity Through Material Choice in Architectural and Urban Design Model-Making - Eduardo Piñones; Rubén Jacob-Dazarola; Marcela Soto; Jorge León; Christopher Nikulin; Cristopher Vrsalovic Rojas; Teresita Marin (Buildings)
This study investigates the impact of conventional versus non-conventional materials on creativity and perceived workload in architectural model-making. Motivated by the need to foster creativity in architectural education, the research hypothesized that unfamiliar materials could stimulate novel design solutions while potentially increasing cognitive and emotional demands. The study was conducted in two phases: defining conventional and non-conventional materials through a survey of architecture professionals and students and a controlled experiment where participants used these materials to create scale models. Creativity was evaluated using Shah’s novelty metric, and workload was measured using the NASA-TLX questionnaire. Results show that models made with non-conventional materials exhibited higher novelty, supporting the hypothesis that unfamiliar materials encourage creative exploration. Surprisingly, perceived workload was lower for non-conventional materials, suggesting that the open-ended nature of the task promoted engagement and alleviated cognitive strain. These findings highlight the potential of non-conventional materials to enhance creativity in architectural education while reducing workload stress, though variability in performance suggests the need for adaptive teaching strategies to support students. Future research should explore how materiality impacts creativity over time in more realistic settings. Additionally, other disciplines supported by physical models during the design process could benefit from similar studies.